(The reality of marriage of writers today (Wisdom, motives and effects - Al Yusuf, Bara‘a Ali (Journal of Islamic Sciences, 2018)
The purpose of lawful marriage is to build a proper Muslim society and to multiply the offspring; with affection, compassion, and tranquility in the spirit of the couple, especially if the spiritual and material factors are at the same level.), Can this marriage achieve the purposes for which it was initiated, as it will be built on the marital union between couples differ in some of the concepts, foundations and standards in life, which may reflect negatively on the education of children in the future, As well as reference to the most important findings of the study of the abhorrence of this marriage, which differs the most important standards and principles between spouses after the research in the jurisprudence views on the subject of study this is what the study tried to answer through Address the issue by demonstrating its judgment from the point of view of Jurisprudence with an explanation of the motives for it, and its wisdom and its implications.
Keywords: Marriage; People of the Book; Deaf people; present; past